Avaliação do eugenol e de óleos essenciais na redução do estresse em aquicultura - Parodi, Thaylise Vey (2014)
This study evaluated the anesthetic efficacy of eugenol and essential oils (EOs) of Aloysia triphylla and Lippia alba on aquaculture, as well as their stress-reducing effect during transport of shrimp and fish. The effectiveness of eugenol on blocking noxious stimulis was also tested. Sub-adult and post-larvae of white shrimp (Litopenaeus vannamei), albine and grey silver catfish (Rhamdia quelen) and fat snook (Centropomus paralellus) were evaluated for anesthetic induction time and recovery during short and long exposure to the EOs and eugenol. Oxidative stress parameters were also evaluated in sub-adult shrimps. Both silver catfish strains and fat snook were transported in water containing EO of A. triphylla at different concentrations and the reduction of stress was evaluated. An experimental model was elaborated to test the analgesic activity of eugenol in zebrafish (Danio rerio). The concentrations of eugenol, EO of A. triphylla and L. alba recommended for anesthesia in shrimps were respectively 200, 300 and 750 μL L-1 for sub-adults and 175, 300 and 500 μL L-1 for post-larvae. The concentrations indicated for transport are between 20-50, 20-30 and 50 μL-1 for sub adults and for post-larvae only eugenol and EO of A. triphylla at 20 and 20-50 μL L-1. A better antioxidant capacity in the hemolymph was obtained with 30 μL L-1 EOs of A. triphylla and L. alba and 20 μL L-1 eugenol. Albine silver catfish juveniles induced and recovered form anesthesia in longer time than grey ones and 200 μL L-1 was considered the most suitable concentration for both strains. In the transport the OE de A. triphylla increased whole body cortisol but did not promote ion loss. The increase of the concentration of OE A. triphylla proportionately decreased and increased the time of induction and recovery from anesthesia in fat snooks. The concentration of 20 μL L-1 reduced blood glucose levels after 24 h and plasma cortisol and lactate levels after 6h. Eugenol itself did not presented analgesic activity, but after the injection of acetic acid in the anterior portion eugenol blocked the noxious reflex.